THE DUAL‐PROCESS DRIFT DIFFUSION MODEL: EVIDENCE FROM RESPONSE TIMES. (4th November 2015) - Caplin, Andrew; Martin, Daniel
Abstract : We introduce a model of response time and choice that borrows from two distinct psychological traditions. As in dual‐process models, rapid (automatic) decisions are qualitatively different from considered decisions. As in the drift diffusion model, delayed (considered) decisions occur when confidence hits a threshold level. We conduct a simple experiment in which our hybrid model matches key properties of the data. As our model predicts, decision times are bimodal, automatic decisions are of far lower quality than considered decisions, and automatic decisions are more prevalent when prior information improves, thereby raising their quality. ( JEL D83, D87, C91)